PENGARUH VEGETASI LANSKAP TERHADAP KENYAMANAN TERMAL SEBAGAI BANGUNAN HEMAT ENERGI DI LINGKUNGAN PERUMAHAN ROYAL SUMATERA - Martha Mulia, Endi; KUSUMA, STEFANNY; Nicholas, Arnold; Eric (Jurnal Sains dan Teknologi ISTP, 2025)
As one of the major urban growth centers in Indonesia, the city of Medan faces significant environmental challenges, including rising temperatures, declining air quality, and limited green open spaces in residential areas. This study examines the influence of landscape vegetation on thermal comfort in Royal Sumatera Housing as part of efforts to realize energy-efficient buildings. The research uses a descriptive qualitative method through observation and the measurement of temperature, humidity, and wind speed within the housing area. The analysis reveals that vegetation such as trees, shrubs, herbs, and bushes positively contributes to reducing temperature and improving thermal comfort, although humidity levels in some areas still exceed ideal standards. Cooler and more consistent wind speeds are also observed in areas with dense vegetation. These findings emphasize the importance of strategic landscape planning in creating thermally comfortable and energy-efficient environments in tropical residential areas.